2007
DOI: 10.1007/s10808-007-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a vapor cavity during explosive boiling on a film microheater: Experiment and numerical simulation

Abstract: Dynamics of formation, growth, and collapse of a vapor cavity during explosive boiling of liquids on film heaters under the action of pulsed heat fluxes q = 10 8 -10 9 W/m 2 is studied theoretically and experimentally. The description of the vapor-cavity formation process is based on the concept of a homogeneous mechanism of nucleation taking into account the influence of already formed and growing bubbles. Evolution of vapor structures is numerically simulated by solving the equations of dynamics of a compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…This is comparable to the heights between 10μm to 70μm found from images in [71]. Varlamov et al [50] show images of a bubble with a height of 40μm for bubble nucleation in ethanol under similar conditions. Asai et al [56] found a bubble height between 70μm and 100μm for boiling in methanol.…”
Section: Bubble Heightsupporting
confidence: 76%
See 3 more Smart Citations
“…This is comparable to the heights between 10μm to 70μm found from images in [71]. Varlamov et al [50] show images of a bubble with a height of 40μm for bubble nucleation in ethanol under similar conditions. Asai et al [56] found a bubble height between 70μm and 100μm for boiling in methanol.…”
Section: Bubble Heightsupporting
confidence: 76%
“…In spite of the extensive research on bubble nucleation and growth in the past there are still a lot of questions on this subject and numbers of papers were written relatively recently on the subject [45,46,47,48,49,50,51]. In each paper a small part of the process is investigated and described, extending the theory somewhat further.…”
Section: Bubble Nucleation and Bubble Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic and kinetic aspects of explosive evaporation of liquids, including the mechanism of boiling incipience, dynamics of vapor cavity evolution, effects of microbubble oscillations and multiple repeated boiling, and pressure and power generation, have been analyzed by many research groups [1,[4][5][6][19][20][21][22][23][24][25][26]. The effect of dissolved gases on boiling incipience temperature, bubble growth, and subsequent evolution of the vapor cavity is of particular importance.…”
Section: Introductionmentioning
confidence: 99%